Комп’ютерні терміни в офіційно-діловому дискурсі: мовностилістичні аспекти - Ментинська, Ірина (Видавництво Львівської політехніки, 2014)
The article is deals with the problems we face in official discourse of the business, including the use of computer terminology in official papers. The attention is drawn to the common errors at the lexical, morphological and syntactic linguistic level.
Keywords: українська мова; офіційно-діловий стиль; дискурс; комп’ютерна термінологія; морфологічні норми; лексичні норми; словотвірні норми; синтаксичні норми